2011
DOI: 10.1063/1.3585694
|View full text |Cite
|
Sign up to set email alerts
|

Ionizing shocks in argon. Part II: Transient and multi-dimensional effects

Abstract: Generation of magnetic field and electrostatic shock wave driven by counterstreaming pair plasmas Phys. Plasmas 10, 392 (2003); 10.1063/1.1540095Modeling argon inductively coupled plasmas: The electron energy distribution function and metastable kinetics

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(20 citation statements)
references
References 12 publications
0
20
0
Order By: Relevance
“…(12), which corresponds to the relative mean kinetic energy. For convenience, we also define an equivalent drift temperature T w = λT 33 , such that all the rates can be tabulated in terms of two temperatures.…”
Section: A Reaction Ratesmentioning
confidence: 99%
See 1 more Smart Citation
“…(12), which corresponds to the relative mean kinetic energy. For convenience, we also define an equivalent drift temperature T w = λT 33 , such that all the rates can be tabulated in terms of two temperatures.…”
Section: A Reaction Ratesmentioning
confidence: 99%
“…The current state of the art for modeling detailed chemical kinetics of a low temperature plasma is the collisionalradiative (CR) model, first proposed by Bates et al in 1962 6,7 . CR models are now commonly used in studies of plasma discharge, plasma-assisted combustion, and hypersonics [8][9][10][11][12][13] . The…”
Section: Introductionmentioning
confidence: 99%
“…In adidition, the governing equations also need to be extended to characterize the thermal non-equilibrium environment of the plasma. Given that the physics has been well established [7,8,3], the extension is certainly achievable.…”
Section: Discussionmentioning
confidence: 99%
“…Fair agreement is found between the simulation results and experimental data. Kapper 164and Cambier[11] have shown that the fluctuations of the shock structure observed experimentally165 can be reproduced by means of unsteady numerical simulations and explained on the basis of the 166 coupling of the nonlinear kinetics of the CR model with wave propagation within the induction zone.167…”
mentioning
confidence: 99%